WEBSITE DESIGN BY APPSERV TUMORITIS THEATRE - Denny Isharmoko; Syahril, SKom Syahril, SKom (Jurnal Sistem Informasi, 2009)
Tumoritis Theatre is a community theater keatif and laboratory creation which seeks to find and create other forms of pronunciation fresh artistic and thematic, are able to build a critical dialectic with the environment.  As a creative community, tumoritis theater is a field that unite people and  critical ideas in creative work with an interdisciplinary approach.  As a laboratory creation of theater, in addition to relying on creative inspiration and anxiety over the problems in the social environment, work tumoritis theater work well approximated  by a spirit of intellectual and interdisciplinary, relying on the research and study on the traditions of theater / performing arts.  One important aspect in the development of information technology role here should really be utilized as a medium of information that a website or sites.